Physical properties of short pineapple leaf fibre (PALF) reinforced high impact polystyrene (HIPS) composites - Siregar, Januar Parlaungan; Salit, Mohd Sapuan; Ab. Rahman, Mohamad Zaki; Mohd Dahlan, Khairul Zaman (Adcotec Ltd., 2009)
The aim of this study to investigate the physical properties of short pineapple leaf fibre (SPALF) reinforced high impact polystyrene (HIPS) composites. Three different sizes of the fibre were used in this study which was 10-40mesh, 40-60mesh and 60-80mesh. A five different fibre contents were used in this study which was 10%, 20%, 30%, 40%, and 50%. The fabricated SPALF/HIPS composites were used melt mixing and compression moulding. The physical properties of SPALF/HIPS composites such as water absorption, thickness swelling, melt flow index (MFI), and density board of composites were studied. The result showed that the addition of the SPALF was decreased the physical properties compare to pure HIPS (0% SPALF).